Ecology of woodland herbs in temperate deciduous forests - Whigham, D.F (Annual review of ecology, evolution, and systematics, 2004)
The diversity of woodland herbs is one of the most striking features of deciduous forests in the temperate zone. Here I review the literature on the ecology of woodland herbs. The review is timely because, since Paulette Bierzychudek's seminal review of the subject in 1982, a number of species have become rare or threatened owing to the conversion of forests to other land uses, competition by alien plant species, and increased abundance of native wildlife that negatively impact woodland herbs (e.g., white-tailed deer). Although the basic biology of woodland herbs is mostly known, few species have been studied in detail, and we are only able to make broad generalities about their ecology. We are especially lacking in information needed to conserve and restore species in altered and threatened habitats.